2012
DOI: 10.1104/pp.112.204438
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Editing and Headgroup Exchange Are the Major Mechanisms That Direct Polyunsaturated Fatty Acid Flux into Triacylglycerols    

Abstract: Triacylglycerols (TAG) in seeds of Arabidopsis (Arabidopsis thaliana) and many plant species contain large amounts of polyunsaturated fatty acids (PUFA). These PUFA are synthesized on the membrane lipid phosphatidylcholine (PC). However, the exact mechanisms of how fatty acids enter PC and how they are removed from PC after being modified to participate in the TAG assembly are unclear, nor are the identities of the key enzymes/genes that control these fluxes known. By reverse genetics and metabolic labeling ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
180
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(185 citation statements)
references
References 39 publications
5
180
0
Order By: Relevance
“…The trafficking of labeled acyl chains from the PL is higher than can be accounted for by efflux of whole lipids, whereas in the GL, it is approximately equal. Membrane Lipid Fatty Acid Moieties Are Incorporated into TG-Membrane lipid acyl chain flux is currently poorly defined both spatially and temporally, yet relies on distinct enzymatic reactions that collectively provide flexibility in lipid metabolic homeostasis (43)(44)(45)(46). The insertion and removal of fatty acids that differ by chain length and number of double bonds defines membrane responses to temperature, salinity, and a variety of other abiotic conditions (47,48).…”
Section: Tg Is Produced Mainly By the Sequential Acylation Of Glyceromentioning
confidence: 99%
“…The trafficking of labeled acyl chains from the PL is higher than can be accounted for by efflux of whole lipids, whereas in the GL, it is approximately equal. Membrane Lipid Fatty Acid Moieties Are Incorporated into TG-Membrane lipid acyl chain flux is currently poorly defined both spatially and temporally, yet relies on distinct enzymatic reactions that collectively provide flexibility in lipid metabolic homeostasis (43)(44)(45)(46). The insertion and removal of fatty acids that differ by chain length and number of double bonds defines membrane responses to temperature, salinity, and a variety of other abiotic conditions (47,48).…”
Section: Tg Is Produced Mainly By the Sequential Acylation Of Glyceromentioning
confidence: 99%
“…Radioisotope labeling of seedlings was adapted from a method reported previously (Bates et al, 2012). Twenty seedlings were used for each sample and grown in media (0.53 MS media with 0.5% sucrose, pH 5.8) in 24-well cell culture plates under 24 h light at 22°C for 10 d. At 3, 6, 10, 30, and 60 min, labeled seedlings were quickly transferred to a tube containing preheated (>75°C) isopropanol with 0.01% butylated hydroxytoluene to stop labeling and lipids were extracted as described previously.…”
Section: Choline and Ethanolamine Labelingmentioning
confidence: 99%
“…In the cytoplasm, the 18:1 from the acylcoenzyme A (CoA) pool is quickly esterified to the phosphatidylcholine (PC) of the endoplasmic reticulum. Desaturation of 18:1 to linoleic acid (LA; 18:2 cis⌬9, 12 ) and then ␣-linolenic acid (ALA; 18:3 cis⌬9, 12,15 ) occurs through the catalytic action of endoplasmic reticulum-localized fatty acid desaturases, the oleate desaturase (FAD2), and the linoleate desaturase (FAD3), producing PUFA-enriched PC (2). It has been shown that PC also is the major site that synthesizes a number of unusual fatty acids, such as hydroxy and conjugated fatty acids (3).…”
mentioning
confidence: 99%